2008
DOI: 10.1016/j.dnarep.2008.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Mrc1, Tof1 and Csm3 inhibit CAG·CTG repeat instability by at least two mechanisms

Abstract: Trinucleotide repeats frequently expand and contract in humans and model organisms. Protein factors that modulate this process have been found by candidate gene approaches or mutant screens for increased expansion rates. To extend this effort, Saccharomyces cerevisiae mutants with higher CAG CTG repeat contraction rates were sought using a disruption library. This screen identified Mrc1, the homolog of human Claspin, which mediates the replication and DNA damage checkpoints, and also couples the replicative he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
35
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 41 publications
8
35
1
Order By: Relevance
“…This effect of the Tof1 knockout on the expansions of a pentanucleotide repeat is quantitatively similar to its effect on trinucleotide repeats (17,29). Thus, functional Tof1 protein precludes expansions of various unstable repeats.…”
Section: Discussionsupporting
confidence: 50%
“…This effect of the Tof1 knockout on the expansions of a pentanucleotide repeat is quantitatively similar to its effect on trinucleotide repeats (17,29). Thus, functional Tof1 protein precludes expansions of various unstable repeats.…”
Section: Discussionsupporting
confidence: 50%
“…It has been reported that TOF1 and CSM3 can cause contraction of (CNG) n trinucleotide repeats and TOF1 along with several checkpoint-related proteins can cause trinucleotide repeat expansion (44). It is possible that such a mechanism could account for the observed changes in telomere length.…”
Section: Discussionmentioning
confidence: 95%
“…Previous results demonstrated that DNA hairpins form in a replicationdependent manner at the ectopic TNRs and that DNA replication origin activity increased the instability of the adjacent hairpinprone TNRs in vivo (56). Since expanded (CTG) n · (CAG) n TNRs are sites of replication fork stalling and genome instability in yeast (30,73,89,90), we tested the effect of (CTG) n · (CAG) n TNRs on replication fork progress and the possible requirement for stabilization of TNR replication by the fork protection proteins Timeless, Tipin, and Claspin. We found that replication forks were stalled by flanking expanded TNRs and that TNR stability was dramatically decreased after knockdown of the replication-forkstabilizing proteins.…”
mentioning
confidence: 99%